2008
DOI: 10.1080/00926230701636197
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia, Emotional Instability, and Vulnerability to Stress Proneness in Patients Seeking Help for Hypersexual Behavior

Abstract: This article reports the findings of a study investigating alexithymia, emotional instability, and vulnerability to stress proneness among individuals (N = 120) seeking help for hypersexual behavior. At the onset of treatment at an outpatient community clinic, subjects completed the Sexual Compulsivity Scale (SCS), the 20-item Toronto Alexithymia Scale (TAS-20), and the NEO Personality Inventory Revised (NEO-PI-R). The results of a hierarchical regression analysis revealed the best model in predicting severity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
67
2
11

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 127 publications
(89 citation statements)
references
References 46 publications
9
67
2
11
Order By: Relevance
“…Reid et al studied patients seeking help for hypersexual behavior and reported that emotional unsteadiness, weakness against stress, and alexithymia are substantially seen in association with hypersexual behavior, and that certain aspects of alexithymia, the inability to identify and describe emotions, had a stronger correlation with the hypersexual disorder (11). Furthermore, evaluation of mindfulness, emotional dysregulation, impulsivity, and stress proneness in people with HD, as compared to normal people, revealed that people with HD have higher scores in problems with emotional regulation, compared to the group of normal people (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reid et al studied patients seeking help for hypersexual behavior and reported that emotional unsteadiness, weakness against stress, and alexithymia are substantially seen in association with hypersexual behavior, and that certain aspects of alexithymia, the inability to identify and describe emotions, had a stronger correlation with the hypersexual disorder (11). Furthermore, evaluation of mindfulness, emotional dysregulation, impulsivity, and stress proneness in people with HD, as compared to normal people, revealed that people with HD have higher scores in problems with emotional regulation, compared to the group of normal people (24).…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature has indicated the potential use of sex as a maladaptive approach, which can alleviate stressful mood conditions or hamper stress (11). Moreover, individuals with hypersexual disorder exhibit several ineffective efforts to manage or reduce the time an individual spends on obsessions with sexual urges, fantasies, and behaviors as the answer to difficult mood conditions or stressful events that occur in life (5).…”
Section: Introductionmentioning
confidence: 99%
“…En su lugar, buscan asistencia por problemas asociados -sobre todo ansiedad, depresión o coadicción a sustancias tóxicas-y el cuadro clínico de CS sólo emerge tras una evaluación exhaustiva. No en vano, estamos hablando de una patología que en la mayoría de ocasiones, lleva aparejados sentimientos de vergüenza y de culpa que difícilmente les permite expresar abiertamente a un desconocido -sea éste o no un profesional de la salud mental-su situación (Reid, 2010;Reid, Bramen, et al, 2014;Reid et al, 2008). El estigma asociado a padecer este tipo de problemas sexuales es si cabe mayor en mujeres, a las que tradicionalmente se las ha considerado promiscuas, adúlteras o degeneradas.…”
Section: Concepto De Compulsividad Sexualunclassified
“…La correspondencia entre esta descripción y algunos síntomas del cuadro clínico de la CS motivó que los primeros estudios sobre personalidad en CS exploraran sobre todo esta dimensión. En el primero de ellos, Reid et al (2008) investigaron la relación entre neuroticismo y CS en un grupo de 120 pacientes (116 hombres y 4 mujeres) en tratamiento por problemas en el control de los impulsos sexuales. A todos ellos se les aplicó el inventario de personalidad NEO PI-R así como la escala SCS de compulsividad sexual, encontrando una correlación de .49 entre neuroticismo y CS y de entre .31 y .48 con las 6 facetes que lo componen (sobre todo con la vulnerabilidad, impulsividad y depresión).…”
Section: La Teoría De Los Cinco Factores (De Ahora En Adelante Ffm Pounclassified
See 1 more Smart Citation